2020
DOI: 10.1108/cr-12-2018-0082
|View full text |Cite
|
Sign up to set email alerts
|

The fit of competitive strategies and firm-specific advantages with country-specific advantages in explaining manufacturing location choices

Abstract: Purpose This paper aims to clarify the fit of competitive strategies and firm-specific advantages (FSAs) with country-specific advantages (CSAs) in explaining manufacturing location choices at product category level in the European automotive industry. Design/methodology/approach Seven hypotheses are formulated and tested using binomial logistic regression with data from 148 passenger car models (i.e. product category level) that are sold in Europe and manufactured in countries that offer CSAs of either cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 77 publications
(176 reference statements)
0
17
0
Order By: Relevance
“…According to Ilmudeen and Bao (2020), the evolving competitive landscape has compelled businesses to understand BIJ 29,10 manufacturing strategies thoroughly. Recently, Akpinar (2020) pointed out the importance of selecting an appropriate manufacturing strategy since its role changes according to economic, technological, and demand conditions, competitors' strengths and weaknesses and product lifecycle. In this vein, several cohort studies have demonstrated that prioritising manufacturing strategy is critical, resulting in improved performance and increasing the company's competitiveness (Ahmad and Schroeder, 2011;Hill and Hill, 2009;Baack and Boggs, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to Ilmudeen and Bao (2020), the evolving competitive landscape has compelled businesses to understand BIJ 29,10 manufacturing strategies thoroughly. Recently, Akpinar (2020) pointed out the importance of selecting an appropriate manufacturing strategy since its role changes according to economic, technological, and demand conditions, competitors' strengths and weaknesses and product lifecycle. In this vein, several cohort studies have demonstrated that prioritising manufacturing strategy is critical, resulting in improved performance and increasing the company's competitiveness (Ahmad and Schroeder, 2011;Hill and Hill, 2009;Baack and Boggs, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…See, for example, Chen (2008) on the factors of activity in international markets. See also Garnett and Pickrell (2010) on the reality of international mergers and Akpinar (2020) on the perspective of advantages in the choice of manufacturing locations.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the extant literature is only dealing with the what and why (Akpinar, 2020;Pavlínek, 2020;Dachs et al, 2019;Wan et al, 2019;Engström et al, 2018;Ketokivi et al, 2017).…”
Section: Purpose Of the Researchmentioning
confidence: 99%
“…Much of the growing body of literature on reshoring relates to the manufacturing industry, but not necessarily to OEMs or AS. However, ten studies are published that cover the automotive industry over a period from 2013 to 2020 and examine competitive strategies to explain manufacturing location decisions (Akpinar, 2020), global production networks (Pavlínek, 2018), international production relocation or re-insourcing as a manufacturing-strategic option (Lampón et al, 2017). The seven remaining studies relate to Lund & Steen (2020), Pavlínek (2020), Moradlou et al (2017), Ocicka (2016), Bailey & De Propris (2014), Drauz (2014 and Schmitt & Van Biesebroeck (2013).…”
Section: Appreciation Of the Automotive Industry In The Literaturementioning
confidence: 99%
See 1 more Smart Citation